The affordances and potentials of mobile digital devices to teach English: a South African case study - Arnold, Luke (School of Education, 2019)
In this paper I attempt to explore the complexities involved in using digital technologies to teach English as home language in a South African private school. For a period of 2 months I conducted ethnographic research at an elite school to best understand the social forces which underlie pedagogic practices and perceptions in such a mainstream educational institution. I recorded my observations with field notes, video data and by collecting several resources produced by students, and focussed on learning interactions which are shaped by technology in some way, most commonly by mobile tablet devices. This project is situated within the research of the New Literacy Studies (Street 1997); it is influenced by the notion social literacies (Gee 1990) and a multimodal approach to learning and teaching (Kress 2005); it understands digital literacy practices in South Africa as unequal and as ‘situated’ (Prinsloo 2005, 2014); finally, it acknowledges technology as a tool within Vygotsky’s activity theory (Jewitt 2007) and as a tool which is used differently by students and teachers (SeftonGreen and Nixon 2009; Merchant, 2007; Rowsell and Marsh, 2011). I aimed to investigate the different ways in which technology is ‘taken up’ by this particular demographic of students, and discuss in what ways these new classroom interactions could contribute to meaningful learning practices. I anticipated that social forces from the top-down and the bottom-up (Sefton-Green and Nixon 2009) would shape and effect digital learning in ways which would either bolster or detract from the curriculum content being imparted. I focus on two main sets of data; the digital productions of a Grade 7 English class, created in class using personal tablet devices; and video data of Grade 7 English class wherein tablet devices are used as a tool for investigating visuals alongside paper-based writing activities. I conduct an in-depth, multimodal analysis of the data to illuminate the complex social – and learning – work taking place as students and teachers interact with each other and digital technologies. In relation to the data analysis I argue that collaborative, creative learning activities shaped around mobile devices are better able to transform English pedagogies rather than learning tasks which switch freely between genres, media and type of activities. I argue that when mobile devices are used during a lesson alongside multiple modes and learning tasks it distracts students and can diverge from the language aims of the lesson. When the teacher gives students freedom to create a personalised, multimodal response to an English text with their mobile devices I argue that digital learning is transformed into a new, fun and meaningful way for students to respond to and personalise curriculum content.